1994
DOI: 10.1111/j.1746-1561.1994.tb06208.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Consequences of Early Initiation of Sexual Intercourse

Abstract: This cross-sectional analysis of the 1991 CDC Youth Risk Behavior Survey explored factors associated with an early age at first sexual intercourse. Almost 18% of White males, 49% of Black males, 5% of White females and 12% of Black females were sexually active before age 13. Carrying a weapon to school, fighting, and early (< age 13) experimentation with cigarettes and alcohol were associated with early initiation of sexual activity for all four race and gender groupings. Those initiating sexual activity early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
5
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(172 citation statements)
references
References 9 publications
12
149
5
6
Order By: Relevance
“…In the present study, the mean age at the first sexual intercourse was 20.85 years compared to 17.6-18.0 years in Northern Thailand (Allen et al, 2003;Liu et al, 2006), 13.0-16.2 in America (Zelnik et al, 1983;Coker et al, 1994;De Genna et al, 2011), 14.0-16.8 in Europe (Andersson-Ellstrom et al, 1996Wellings et al, 1996;Edgardh, 2000;Woynarowska et al, 2006;Panatto et al, 2012) and 13.5-17.8 in Africa (Kayembe et al, 2008 ;Dingeta et al, 2012;Doku, 2012;Remes et al, 2012). The delay of first sexual intercourse in the current study may have been influenced by Thai traditional culture, in which early experience with sexual intercourse is considered socially unacceptable (Sridawruang et al, 2010;Supametaporn et al, 2010).…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In the present study, the mean age at the first sexual intercourse was 20.85 years compared to 17.6-18.0 years in Northern Thailand (Allen et al, 2003;Liu et al, 2006), 13.0-16.2 in America (Zelnik et al, 1983;Coker et al, 1994;De Genna et al, 2011), 14.0-16.8 in Europe (Andersson-Ellstrom et al, 1996Wellings et al, 1996;Edgardh, 2000;Woynarowska et al, 2006;Panatto et al, 2012) and 13.5-17.8 in Africa (Kayembe et al, 2008 ;Dingeta et al, 2012;Doku, 2012;Remes et al, 2012). The delay of first sexual intercourse in the current study may have been influenced by Thai traditional culture, in which early experience with sexual intercourse is considered socially unacceptable (Sridawruang et al, 2010;Supametaporn et al, 2010).…”
Section: Discussionmentioning
confidence: 41%
“…Biologically, we found that early sexual activity after menarche (< 6 years) led to greater susceptibility to SCCA. During puberty, the immaturity of cervical cells undergo many changes that might be more vulnerable to damage and HPV infection and/or other sexually-transmitted diseases (Coker et al, 1994;Kahn et al, 2002;Collins et al, 2005;Matos et al, 2005;Louie et al, 2009). This data indicates that a delay of 6 or more years after menarche before sexual intercourse would be safer and afford some protection from sexually-transmitted diseases (including HPV infection) and susceptibility to cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier first sexual intercourse (FSI) is associated with unprotected intercourse, 1 inconsistent contraceptive use, 2 and multiple partners and with negative social and health outcomes, including partner violence, 3 lower educational attainment, 4,5 unintended pregnancy, teenage parenting, 6 and sexually transmitted infection. 7,8 Definitions of "early" FSI have varied, and include age 15 years and younger 2,4,9 or 16 years and younger, 7,10 or quartiles or tertiles of age at FSI in a study population. 11,12 Previous prospective studies have demonstrated that a range of biological, social, and psychological precursors such as early puberty, childhood adversity, low socioeconomic status, dysfunctional family relationships, absence of a biological father at home, poor school adjustment, adolescent depression, and low self-esteem are associated with earlier age at FSI.…”
Section: What This Study Addsmentioning
confidence: 99%
“…28,29 In brief, the cohort was recruited during pregnancy from the single tertiary-catchment maternity hospital in Western Australia, with clinical and questionnaire data collected at 18 and 34 weeks' gestation. Study children and their families were then followed up at ages 1, 2, 3, 5, 8, 10, 14, and 17 years with extensive clinical and questionnaire data collected, including behavioral assessments (2,5,8,10,14, and 17 years), and sexual behavior (17 years). Informed consent was obtained at the time of study enrolment and at every subsequent follow-up.…”
Section: Participantsmentioning
confidence: 99%
“…Estos resultados se encuentran en consonancia con lo reportado por otros autores, tanto nacionales como extranjeros ( 6,12,24,25 ).…”
Section: Discussionunclassified